Fresno County Bar Association February Bar Luncheon with Harvey Rosenfield-Prop. 103 Author - Watkins, Howard::::::::: (1989)
Fresno County Bar Association President Dana French, Harvey Rosenfield, and Fresno County Bar Association President-Elect Thomas Tusan